2009
DOI: 10.1039/b908625k
|View full text |Cite
|
Sign up to set email alerts
|

Dialysis process for the removal of surfactants to form colloidal mesoporous silica nanoparticles

Abstract: Colloidal mesoporous silica nanoparticles less than 20 nm in diameter are prepared by dialysis; this simple surfactant removal route can avoid aggregation by sedimentation-redispersion and remove cationic surfactants while retaining the original colloidal state, which is applicable to the preparation of primary nanoparticles carrying a functional organic substance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
95
0
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 121 publications
(107 citation statements)
references
References 37 publications
6
95
0
3
Order By: Relevance
“…A close examination of TEM showed that these nanoparticles are porous silica with wormlike holes ( Figure S6 in the Supporting Information). [47] As is already known, the dissolution rate of silica nanoparticles drastically depends on the size of particles, alkalinity, and reaction temperature. [13] It is important to note that, before and after crystallization, the pH of the system remained constant, close to 11.5.…”
Section: Resultsmentioning
confidence: 97%
“…A close examination of TEM showed that these nanoparticles are porous silica with wormlike holes ( Figure S6 in the Supporting Information). [47] As is already known, the dissolution rate of silica nanoparticles drastically depends on the size of particles, alkalinity, and reaction temperature. [13] It is important to note that, before and after crystallization, the pH of the system remained constant, close to 11.5.…”
Section: Resultsmentioning
confidence: 97%
“…In this method, colloidal mesostructured silica nanoparticles were dialyzed against a 2 M aqueous acetic acid and ethanol (v:v = 1:1) solution to remove the templates ( Figure 6). 80 But, the dispersibility of mesostructured silica nanoparticles can be preserved after the removal of templates. In addition, this method overcomes the above-mentioned disadvantages of the conventional redispersion process for the preparation of colloidal MSNs.…”
Section: Preparative Methods Of Colloidal Msns Without Any Aggregatiomentioning
confidence: 99%
“…100 nm in diameter are expected to be useful for applications in DDS and transparent media such as low-refractive index materials, thermal insulation films, and low dielectric materials [6][7][8][9][10][11][12][13][14]. However, it has been difficult to synthesize monodisperse porous silica particles of 100 nm in diameter on an industrial scale, because the synthesis should take place in highly diluted solutions [10,[15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30]. We recently reported the large-scale synthesis of monodisperse microporous silica particles of 100 nm in diameter [31], based on the modified Stöber method [32].…”
Section: Introductionmentioning
confidence: 99%